Technical nursing students interacting with family members of hospitalized children - Juliana Yukari Takahashi Onishi; Circéa Amália Ribeiro; Maria Cristina Ferreira Carlos Rodrigues da Silva; Regina Issuzu Hirooka de Borba
ABSTRACT Objective: To understand technical nursing students' meaning of interacting with family members of hospitalized children. Method: Symbolic Interactionism was used as the theoretical framework and Qualitative Content Analysis was the methodological procedure. A total of eight graduates from an institution situated in the city of Osasco, Sao Paulo state, participated in this study. Data were collected through semi-structured interviews. Results: A total of five representative themes were revealed: Dealing with difficult situations with family members; Perceiving oneself to be unprepared to interact with family members; Family members being a helpful tool; Developing strategies to obtain a good interaction with family members; and Teachers being facilitators of the interaction with family members. Final considerations: To be acquainted with this experience has led to the understanding of the need to include the theme of family care in the curriculum of the Technical Nursing Course. Additionally, the present study contributed to reflections on the importance of such knowledge for this population and to the development of future studies, as this theme has been scarcely explored in the literature.